Diagnostic value of superficial cultures for late-onset sepsis - Adedeji, Babatunde Kayode-; Nair, V; Wood, K Harvey-; Loganathan, Prakash (Indian Journal of Child Health, 2017)
Background: Late-onset sepsis (LOS) is associated with poor outcome and one of the prevalent causes of death in preterm population; hence, there is always a need for early prediction of sepsis. The performance of routine superficial swab culture is one of the strategies for the early prediction and may help in the selection of appropriate empirical antibiotics. Objective: The purpose of the study is to evaluate the diagnostic value of superficial swab cultures for LOS. Methods: We conducted a retrospective cohort study (November 2015-October 2016) in a tertiary neonatal intensive care. Inclusion criteria were preterm infants with gestationalage ?34 weeks with a diagnosis of sepsis (culture-positive and culture-negative clinical sepsis). In our unit, weekly surveillance swab cultures (skin swab, mouth swab, nasopharyngeal aspirate, and umbilical surface swab) are taken from all admitted neonates, and usually, no interventions are carried out based on these culture results. We excluded infants with surgical diagnosis/congenital anomalies and infants with early-onset sepsis. Results: After exclusion, there were 38 preterm infants fulfilling our inclusion criteria; among them, there were 108 LOS episodes. Blood culture was positive in 33 episodes, and Staphylococcus epidermidis (21%) was the most common organism cultured. In our study, superficial swab cultures had a very low diagnostic value, as sensitivity (42.9%), specificity (28.7%), predictive values, and likelihood ratio that all the estimations were low. Conclusions: Superficial swab cultures are associated with low diagnostic value for LOS. Superficial swab culture may be used surveillance of colonizing organism in the neonatal unit and provides antibiotic sensitivity pattern.